Self-trapping of a binary Bose-Einstein condensate induced by interspecies interaction - Adhikari, Sadhan Kumar [UNESP] (Iop Publishing Ltd, 2011)
The problem of self-trapping a Bose-Einstein condensate (BEC) and a binary BEC in an optical lattice (OL) and double well (DW) is studied using the mean-field Gross-Pitaevskii equation. For both DW and OL, permanent self-trapping occurs in a window of the repulsive nonlinearity g of the GP equation: g(c1) < g < g(c2). In the case of OL, the critical nonlinearities gc1 and gc2 correspond to a window of chemical potentials mu(c1) < mu < mu(c2) defining the band gap(s) of the periodic OL. The permanent self-trapped BEC in an OL usually represents a breathing oscillation of a stable stationary gap soliton. The permanently self-trapped BEC in a DW, on the other hand, is a dynamically stabilized state without any stationary counterpart. For a binary BEC with intraspecies nonlinearities outside this window of nonlinearity, a permanent self-trapping can be induced by tuning the interspecies interaction such that the effective nonlinearities of the components fall in the above window.